Alexius Meinong’s Theory of “Personal Value" in the Context of Axiological Discourses - Norkus, Zenonas (Problemos, 1995)
The main problems of the philosophical value theory (axiology) are: (1) is value ontologically dependent on the being?; (2) is value ontologically dependent on the valuing subject?; (3) is value epistemologically dependent on the valuing subject? The classical spiritualism basing itself on the thesis of the identity of the being, mind and value answers, affirmatively the question (1) and gives negative answers to the questions (2) and (3). The classical naturalism affirms (1) and (2) but denies (3). Postclassical relativism in the value theory answers all three questions affirmatively while postclassical axiological absolutism gives to all of them negative answers. The author analyses the theory of the Austrian philosopher A Meinong (1853-1920) as a representative of the early (‘psychologistic’) postclassical axiological relativism Thus theory is the result of an attempt to generalize the economic theory of the “marginal utility”. It is argued that mature “antipsychologistic” axiological relativism (as distinguished from the early “psychologistic” one) makes the distinction between the valuation as competence and valuation as performance. The first is the subject of the logic of valuation and decision. The second is the subject of the empirical (the psychology including) research.